1997
DOI: 10.1159/000119327
|View full text |Cite
|
Sign up to set email alerts
|

Active Avoidance Learning Using Brain Stimulation Applied to the Inferior Colliculus as Negative Reinforcement in Rats: Evidence for Latent Inhibition

Abstract: The inferior colliculus has been implicated in aversive or anxiogenic aspects of defensive behavior. Animals learn to turn off electrical stimulation applied to the inferior colliculus. The purpose of the present study was to determine (1) whether this aversion induced by electrical stimulation can be conditioned to a conditioned stimulus (CS, light) and (2) whether pre-exposure to the CS will diminish the extent of such conditioning, i.e. whether latent inhibition can be established with this paradigm. Rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 21 publications
2
4
0
2
Order By: Relevance
“…The rats increased their rate of responding in the presence of light over a number of trials. This effect may not be attributed to reflexive motor responses, since it was not observed when the neutral stimulus was presented alone, as demonstrated in a previous study from this laboratory (10). The pattern of results obtained in the present experiments with light as a warning stimulus parallels those which use a conditioned stimulus paired with stimulation of the dorsal periaqueductal gray (19,20).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The rats increased their rate of responding in the presence of light over a number of trials. This effect may not be attributed to reflexive motor responses, since it was not observed when the neutral stimulus was presented alone, as demonstrated in a previous study from this laboratory (10). The pattern of results obtained in the present experiments with light as a warning stimulus parallels those which use a conditioned stimulus paired with stimulation of the dorsal periaqueductal gray (19,20).…”
Section: Discussionsupporting
confidence: 84%
“…The brain stimulation was applied at a current intensity 5% below the escape threshold previously determined in the open-field. The adequacy of this current intensity level for the escape response was chosen on the basis of previous studies from our laboratory (5,10).…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…Moreover, systemic or local injections of GABA agonists or benzodiazepines into this midbrain structure promptly reduce the aversive consequences of their electrical stimulation (Melo et al, 1992;Pandossio and Brandão, 1999). As GABA receptor antagonists mimic the effects of the electrical stimulation, it has been suggested that the neural substrate of aversion in this midbrain region be under GABAergic tonic inhibitory modulation (Melo et al, 1992;Brandão et al, 1988Brandão et al, , 1993Brandão et al, , 1994Brandão et al, , 1997. Local injections of serotonergic agents known for their antiaversive action when injected in other structures of the brain aversion system also decrease the aversiveness of the exposure of rats to the elevated plus-maze test (Melo and Brandao, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The brain stimulation was applied at a current intensity 5% below the escape threshold previously determined in the open field. The adequacy of this current intensity level for the escape response was verified on the basis of a previous study from this laboratory (Melo et al, 1992;Brandão et al, 1997;Troncoso et al, 1998).…”
Section: Apparatusmentioning
confidence: 92%
“…Furthermore, electrical stimulation of the dorsal periaqueductal gray and inferior colliculus has consistently been shown to induce aversive effects, because it elicits defensive behaviors. Moreover, electrical stimulation sustained learned operant escape responses and also supported learning of conditioned emotional responses (14).…”
mentioning
confidence: 88%